Age and type of aphasia in patients with stroke. Issue 5 (May 1981) - Eslinger, P J; Damasio, A R
Abstract : The age and gender of a series of patients with different types of aphasia were analysed. Regardless of gender, patients with Broca and conduction aphasias were significantly younger than those with Wernicke and global aphasias. Considering the established cerebral localisation of each of those aphasia types, it appears that, with age, stroke in the territory of the middle cerebral artery will tend to either shift posteriorly (producing Wernicke aphasia) or occupy most of the middle cerebral artery territory (producing global aphasia). But in the absence of concurrent verification of the locus of lesion in each of the cases in our sample, a possible alternative hypothesis must be entertained: that there might be age-related changes in the neurophysiological mechanism subserving language, such that some types of aphasia would tend to be more prevalent with age, regardless of lesion location.